SIRT1 Deacetylates TET2 and Promotes Its Ubiquitination Degradation to Achieve Neuroprotection Against Parkinson's Disease - Li, Xuan; Liu, Te; Wu, Ting-Ting; Feng, Ya; Peng, Si-Jia; Yin, Huiyong; Wu, Yun-Cheng (Frontiers in Neurology, 2021)
The epigenetic modifications, such as DNA methylation and histone acetylation, play a critical role in the pathogenesis of Parkinson's disease (PD). However, the relationship between DNA methylation and histone acetylation in PD is not fully understood. Previous studies have shown that patients with PD exhibit an epigenetic and transcriptional upregulation of Ten-Eleven Translocation 2 (TET2), a member of the DNA hydroxylases family. Silence information regulator 1 (SIRT1), a nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylase, also plays a critical role in PD development and might be a potential target for PD therapy. Our previous data indicated that demethylation in the Cyclin-dependent kinase inhibitor 2A (CDKN2A) promoter by the TET2 directly activated its expression, then promoted the cell cycle arrest and cell death induced by 1-methyl-4-phenyl-pyridinium ion (MPP+). In this study, we found that the enzyme activity of SIRT1 is negatively correlated with the protein level of TET2. In addition, the deacetylation of TET2 induced by SIRT1 promotes TET2 degradation via the ubiquitin–proteasome pathway. Furthermore, the activation of endogenous SIRT1 by resveratrol (RV) leads to CDKN2A DNA hypermethylation due to the decreased TET2 protein levels, which relieves the inhibitory effect on CDK4 and upregulation of pRb, allowing cell proliferation and growth. Similar effects are observed for the inhibition of endogenous TET2 enzyme activity with TET2 inhibitor. Together, we discover a new mechanism by which the SIRT1-TET2-CDKN2A pathway is involved in the pathogenesis of PD, which may provide a potential target for PD treatment.